2006
DOI: 10.1590/s0101-20612006000300026
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-química de okara e aplicação em pães do tipo francês

Abstract: RESUMOA composição química do extrato aquoso de soja e de seu subproduto okara foi determinada. Em base seca, para o okara, o teor dos componentes encontrados foi de 2,8% de cinzas, 37% de proteínas, 13% de lipídios, 42,5% de fibras alimentares e 4,7% de carboidratos solúveis. Para o extrato aquoso esses valores foram de 2,4% de cinzas, 33% de proteínas, 17,7% de lipídios, 41,4% de carboidratos solúveis e traços de fibras alimentares. Pães do tipo francês foram adicionados de 0, 5, 10 e 15% de okara seco. Foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 14 publications
1
21
0
14
Order By: Relevance
“…The data of loss of weight during cooking agreed with the values found for the percent loss of juice exuded in (1981), respectively, but two times lower than the values 42.5 g.100 g -1 and 54.3 g.100 g -1 found by Bowles and Demiate (2006) and Mateos-Aparicio et al (2010), respectively, in similar materials. The probable explanation for the large difference in the fiber content between similar materials is the analysis procedure.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The data of loss of weight during cooking agreed with the values found for the percent loss of juice exuded in (1981), respectively, but two times lower than the values 42.5 g.100 g -1 and 54.3 g.100 g -1 found by Bowles and Demiate (2006) and Mateos-Aparicio et al (2010), respectively, in similar materials. The probable explanation for the large difference in the fiber content between similar materials is the analysis procedure.…”
Section: Resultssupporting
confidence: 85%
“…The probable explanation for the large difference in the fiber content between similar materials is the analysis procedure. Mateos-Aparicio et al (2010) and Bowles and Demiate (2006) used the enzymatic-gravimetric method, whereas in the present study the procedure used was the Van Soest method with neutral detergent without the use of enzymes. Moreover, the greater fiber content found in the industrial residue A, when compared to that found by Aguirre et al (1981) and that in residue B, could be explained by the production system used to prepare the soymilk.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The okara protein is of extremely high quality and the amino acid profile, determined by the Protein Efficiency Ratio (PER), is slightly superior to that of the soymilk itself, according to reports by Hackler et al (1963) and Travaglini et al (1980a,b). In addition, Bowles and Demiate (2006) and Jackson et al (2001) showed that approximately 1/3 of the isoflavones present in the soybean remains in the okara, 2005), lipid content by the Bligh-Dyer method (CECHI, 1999) The determinations were performed in triplicate and the results expressed in dry weight basis (dwb) or wet weight basis (wwb).…”
Section: Introductionmentioning
confidence: 99%
“…It also can be used in products such as granola, ice-creams, chocolates, cakes, breakfast cereals, snacks, candies and biscuits, such as flour or "milk" (CAMARGO; CASTRO;GAVILANES, 2000;VILHENA, 2004;BOWLES;DEMIATE, 2006;FERBERG et al, 2006).…”
Section: Introductionmentioning
confidence: 99%